THE IMPLEMENTATION OF COOPERATIVE MODEL OF MISSOURY TYPE OF MODIFIED MATHEMATICS PROJECT CONCERNING COGNITIVE STYLE (EXPERIMENT STUDY ON LINES AND ANGLES MATERIAL OF CLASS VII AT MTS. MUALLIMIN MUHAMMADIYAH IN MAKASSAR - Nur Iffah (Universitas Negeri Makassar, 2016)
The Research is Quasi Experiment which aims to discover whether learning model and cognitive style influenced mathematics learning results of class VII student at MTs. Muallilimin Muhammadiyah Makassar. The populations on the research were all students at MTs. Muallimin Muhammadiyah in Makassar consisted of three classes in academic year 2015/2016. The samples were determined by using cluster random sampling technique. The samples chosen were class VII A and VII C with 38 students in class VII A and 34 students in class VII C. There were two variables in the research, namely: (1) independent variables consisted of learning model and cognitive style and (2) dependent variable was the students’ learning result in mathematics. The intended learning model is cooperative model of MMP type modified with STAD learning model and cognitive model of MMP typed modified with TAI types; whereas, the intended cognitive style is reflective and implsive cognitive style. The instrument of the resrch were MFFT cognitive style test and test of mathematics learning result. The data of research was analyzed by using descriptive and inferential statistic analysis by using independent sampel t test analysis. The result of the research reveal that there is no difference f Mathematics learning result of student who were taught by using cooperative model of MMP type modified with STAD type student taught by using cooperative model on MMP type modified with TAI type, there is no difference of learning result of students who have reflction cognitive and students who have impulsive cognitive style on the implementation of cooperative model of MMP type modified with STAD type, and there is no difference of learning result of students who have reflective cognitive style and the students who have impulsive cognitive style type on the implementation of cooperative model of MMP type modified with TAI type